Cost-Effectiveness of the FDA Menu Labeling to Reduce Obesity-Associated Cancer Burden in the United States. (29th May 2020) - Du, Mengxi; Griecci, Christina; Cudhea, Frederick; Eom, Heesun; Wong, John; Wilde, Parke; Kim, David; Rehm, Colin; Michaud, Dominique; Wang, Y Claire; Mozaffarian, Dariush; Zhang, Fang Fang
Abstract: Objectives: The FDA menu labeling policy requires chain restaurants with ≥20 outlets to list total calories on menus or menu boards. While obesity is a known risk factor for 13 cancers, the potential impact of this policy on cancer burdens and healthcare costs in the US is unknown. Methods: Using a probabilistic cohort state-transition model, we estimated the health impacts, costs, and cost-effectiveness of the FDA menu labeling policy on reducing calorie intake, subsequent weight change, and obesity-related cancer cases among US adults over a lifetime. Baseline demographics and calorie intake from restaurants were estimated using NHANES 2013–2016. Based on published meta-analyses, we assumed that labeling would reduce calorie intake per meal by 7.3%, evaluated with and without an additional 5% reduction through industry reformulations; and assumed only half of these calorie reductions would be sustained by individuals throughout their day (i.e., to account for potential calorie compensation outside restaurants). Changes in BMI were derived from published energy models (0.45 kg lower long-term weight per 55 kcal/d calorie reduction). National cancer rates and healthcare costs were obtained from published sources. Uncertainties of inputs were incorporated in probabilistic sensitivity analyses using 1000 simulations. Results: The FDA menu labeling policy was estimated to prevent 31, 300 (95% UI: 27, 600–35, 500) new cancer cases and 18, 700 (16, 400–21, 300) cancer deaths, gaining 134, 000 (117, 000–153, 000) quality-adjusted life years (QALYs) among US adults over a lifetime. Top three cancers prevented were endometrial, post-menopausal breast, and kidney. Accounting for policy implementation and healthcare costs, the policy was net cost saving at 1.74B (1.55–1.95B) and 1.76B (1.46–2.09B) from healthcare and societal perspectives, respectively. A modest industry response (5% calorie reduction) would prevent a total of 51, 800 new cancer cases (47, 900–56, 400) and 30, 900 cancer deaths (28, 600–34, 000) and increase net savings to 2.87B (2.68–3.12B) and 3.19B (2.86–3.54B), respectively. Conclusions: Our model suggests implementation of the FDA menu calorie labeling policy would substantially reduce incident cancers and deaths and be cost-saving, with even larger effects if accompanied by modest industry reformulation. Funding Sources: NIH/NIMHD.